Study on the Tooth Tip Sharpening of Face Gear with Circular Arc Profile - Sheng Wei; Feng Zhanrong; Wang Lixia; Zou Meng (Jixie chuandong)
Considering the advantages of the circular arc gear and the face gear,the gear drive with circular arc tooth profile is put forward. In order to advance the machining application of the face gear,the face gear blank size must be determined. By using the envelope forming theory,the tooth surface equation of the circular arc tooth profile is deduced,and the contour visualization is realized in MATLAB,and it is concluded that the tooth tip has two sharpening in the radial direction. The factors that affect the radius of the tooth tip sharpening are analyzed and calculated according to the numerical calculation. A special case with a helix angle of 0° is proposed and the approximate equation of inner diameter and outer diameter of tooth tip sharpening is obtained by least squares method. Finally,the feasibility of the theoretical calculation and the approximate equation is proved by the simulation experiment.